Spontaneous rupture of pregnancy luteoma - Bahat, Pınar Yalçın; Çetin, Berna Aslan; Turan, Gökçe (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Luteoma is a rare condition in pregnancy. In this article, we aimed to present a rare case of pregnancy luteoma detected during cesarean section and pathologically in the context of literature information.